Nondestructive rare earth element imaging of fish teeth from deep‐sea sediments. (21st April 2015) - Sun, Pengfei; Deng, Biao; Du, Guohao; Li, He; Sun, Weidong; Ren, Jiangbo; Xiao, Tiqiao
<x xml:space="preserve">Abstract</x> X‐ray fluorescence computed tomography is an emerging imaging modality that allows for the nondestructive reconstruction of the internal distribution of elements within a sample. The common use of X‐ray excitation energy (up to approximately 20 keV) has necessitated the use of l‐shell fluorescence for heavy elements. In this study, based on high energy X‐ray at BL13W1 of the Shanghai Synchrotron Radiation Facility, we employed high‐energy excitation for tomographic imaging of the heavy metals (rare earth elements) in fish teeth from deep‐sea sediments on the micrometer scale using K‐shell X‐ray fluorescence. The virtual cross‐sectional distribution of La, Ce, Pm, Pr, Nd, and Sm were obtained, thereby providing a feasible approach for analyzing the enrichment mechanism of rare earth elements. Copyright © 2015 John Wiley & Sons, Ltd.